Implement of Smart Health Care Monitoring System using Mobile IoT and Cloud Computing Technologies - Rajaram, Dr. J; Navya, D; Krishna, E; Harika, G (The journal of contemporary issues in business and government, 2020)
Recently, many research works were interested in combining cloud computing and IoT to design systems for smart health care. Many authors have highlighted the benefits of using cloud computing with IoT and proposed a cloud infrastructure to extend the limited resources of the sensors and to facilitate the management of the sensor-centric applications in many domains. However, about MCIoT convergence, there are fewer research works. One of the projects is about a developed platform based on MCIoT where sensors can interact with a mobile device which has access to the cloud via Internet using Bluetooth. Based on restful web services, the framework is feasible on resource constrained devices. Our work aims basically to come up with a general service architecture for smart healthcare monitoring application, that combines the features of mobile devices, sensors, and cloud computing to offer to the user the enhanced services that are accessible anywhere while guaranteeing scalability and security. Our general service architecture to build a network for health care applications that generated data is stored in the cloud our mobile application will show the accurate results on user dashboard of their smartphones.